Cross-cultural adaptation and measurement properties of the Portuguese version of the Ankle Instability Instrument - Silva, Diogo C.F.; Vilas-Boas, João Paulo; Carvalho Mesquita, Cristina; Maia, José; Santos, Rubim; Teixeira Peixoto, Tiago André; Brito, Nuno; Sousa, Andreia S.P. (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Chronic ankle instability is one of the most common clinical conditions in the general population, especially in adult athletes. The cross-cultural adaptation of self-reported questionnaires that identify and classify this condition contribute to criteria standardization in research but also in rehabilitation. Aim of Study. To validate the Ankle Instability Instrument to the Portuguese population and to investigate its psychometric properties. Material and Methods. Linguistic and semantic equivalence of the original version of the Ankle Instability Instrument to the Portuguese population was firstly performed. The Portuguese version of the Ankle Instability Instrument was then applied to 81 higher education adult students, with (n = 59) and without history of ankle sprain (n = 22). Participants were evaluated two times with an interval of one week to assess the psychometric properties of the Portuguese version of the Ankle Instability Instrument. Results. In the reliability of binary responses based on the test-retest, the tetrachoric correlation coefficient ranged from 0.99 to 1.00. In addition, the Kuder–Richardson coefficient was 0.79 suggesting good internal consistency. Conclusions. Test-retest showed an almost perfect match in all answers between the two moments, which seem to be related to sample characteristics. The internal consistency value was similar to the one obtained in the original version. The Portuguese version of the Ankle Instability Instrument is highly reliable and can be used in clinical practice.
Keywords: chronic ankle instability; self-reportedquestionnaire; reliability; cross-cultural adaptation